Epigenetic regulation of gene responsiveness in Arabidopsis - To, Taiko K.; Kim, Jong-Myong (Frontiers in Plant Science, 2014)
The regulation of chromatin structure is inevitable for proper transcriptional response in eukaryotes. Recent reports in Arabidopsis have suggested that gene responsiveness is modulated by particular chromatin status. One such feature is H2A.Z, a histone variant conserved among eukaryotes. In Arabidopsis, H2A.Z is enriched within gene bodies of transcriptionally variable genes, which is in contrast to genic DNA methylation found within constitutive genes. In the absence of H2A.Z, the genes normally harboring H2A.Z within gene bodies are transcriptionally misregulated, while DNA methylation is unaffected. Therefore, H2A.Z may promote variability of gene expression without affecting genic DNA methylation. Another epigenetic information that could be important for gene responsiveness is trimethylation of histone H3 lysine 4 (H3K4me3). The level of H3K4me3 increases when stress responsive genes are transcriptionally activated, and it decreases after recovery from the stress. Even after the recovery, however, H3K4me3 is kept at some atypical levels, suggesting possible role of H3K4me3 for a stress memory. In this review, we summarize and discuss the growing evidences connecting chromatin features and gene responsiveness.